Milking the Cow: Cattle-Derived Chimeric Ultralong CDR-H3 Antibodies and Their Engineered CDR-H3-Only Knobbody Counterparts Targeting Epidermal Growth Factor Receptor Elicit Potent NK Cell-Mediated Cytotoxicity - Pekar, Lukas; Klewinghaus, Daniel; Arras, Paul; Carrara, Stefania C.; Harwardt, Julia; Krah, Simon; Yanakieva, Desislava; Toleikis, Lars; Smider, Vaughn V.; Kolmar, Harald; Zielonka, Stefan (Frontiers in Immunology, 2021)
In this work, we have generated epidermal growth factor receptor (EGFR)-specific cattle-derived ultralong CDR-H3 antibodies by combining cattle immunization with yeast surface display. After immunization, ultralong CDR-H3 regions were specifically amplified and grafted onto an IGHV1-7 scaffold by homologous recombination to facilitate Fab display. Antigen-specific clones were readily obtained by fluorescence-activated cell sorting (FACS) and reformatted as chimeric antibodies. Binning experiments revealed epitope targeting of domains I, II, and IV of EGFR with none of the generated binders competing with Cetuximab, Matuzumab, or EGF for binding to EGFR. Cattle-derived chimeric antibodies were potent in inducing antibody-dependent cell-mediated cytotoxicity (ADCC) against EGFR-overexpressing tumor cells with potencies (EC50 killing) in the picomolar range. Moreover, most of the antibodies were able to significantly inhibit EGFR-mediated downstream signaling. Furthermore, we demonstrate that a minor fraction of CDR-H3 knobs derived from generated antibodies was capable of independently functioning as a paratope facilitating EGFR binding when grafted onto the Fc part of human IgG1. Besides slightly to moderately diminished capacities, these engineered Knobbodies largely retained main properties of their parental antibodies such as cellular binding and triggering of ADCC. Hence, Knobbodies might emerge as promising tools for biotechnological applications upon further optimization.